Model Pembelajaran Atletik Melalui Permainan Bintang Beralih bagi Peserta didik Madrasah Ibtidaiyah Miftahul Huda Tamansari Mranggen Kabupaten Demak - Purwito, Ahmad; Suripto, Agus Widodo (Universitas Negeri Semarang, 2023)
Efforts to improve the quality of education are certainly inseparable from learning facilities, that the development of learning models urgently needs to be done by educator teachers to improve the learning process that is interesting and fun for students. In the method of development research with sequence. research and data collection, planning, product draft development, initial field trials (small-scale trials), revision of small-scale trials to improve trial results, large-scale field trials conducted through interview questionnaires and analysis of results. From the results of the study on the validation of the expert tailor showed a percentage of 84%. During a small-scale trial, the results of the student study questionnaire showed a presensatse of 95% with a sample of 25 6th grade students and a large group test showed a percentage of 99% with a sample of 29 6th grade students and until the print of the product. The results can be concluded on large group tests on athletic learning models through star switching effectively conducted with large group tests. And can be revised the product if it needs to be revised and can be continued on the product feasibility test. In large-scale tests this time the study did not experience problems or obstacles. And from the team of expert validators this research has been felt good and can be continued to print the product.